Higher education and research in the Brexit policy process. - Corbett, Anne; Hantrais, Linda (Journal of European Public Policy, 2023)
This article on post-Brexit policies for higher education and research suggests that these public policy domains are characterised by their intellectual independence from the state or market. The authors see a legacy of the UK's historical relationship with the EU in its treatment of the two epistemically linked domains, reflecting institutional differences. UK governments have generally been wary of EU involvement in higher education and supportive of research collaboration. Post-Brexit evidence suggests that the UK has been purposively 'de-Europeanising' higher education for the supposed gains of marketised international policy. But the UK is also a victim of its overarching Brexit policy, which risked failing to secure associate status for the UK in the EU's world famous Horizon Europe science programme. The article explores the question of whether Brexit caused divergence in these sectors or whether it provided the opportunity for the UK government to solidify an already semi-autonomous policy trajectory.